Ecosocial change and community resilience: The case of "Bönan" in glocal transition. Issue 3 (2nd October 2019) - Rambaree, Komalsingh; Sjöberg, Stefan; Turunen, Päivi
ABSTRACT: The aim of this article was to identify and discuss ecosocial changes and community resilience mechanisms in a coastal fishing community of Sweden – Bönan. Data were collected through eight semi-structured interviews and field observations. An abductive thematic analysis was used to analyze data and background literature. The findings showed that Bönan has been exposed to a combination of ecosocial changes that have transformed the community, and therefore required community resilience interventions. This article concludes that social workers need to take an active part in ecosocial work for enhancing community resilience.